Fabrication of silicon aperture probes for scanning near-field optical microscopy by focused ion beam nano machining - Lehrer, C.; Frey, Lothar; Petersen, S.; Sulzbach, T.; Ohlsson, O.; Dziomba, T.; Danzebrink, H.; Ryssel, Heiner (Microelectronic Engineering, 2001)
Scanning near-field optical microscopy (SNOM) probes can be realized by aperture probes based on metal coated atomic force microscopy (AFM) sensors. The application of focused ion beam (FIB) nano machining for the fabrication of apertures with well defined geometry and dimensions down to 60 nm will be described. Problems related to the processing of laterally and vertically well defined structures will be discussed. Apertures with circular and rectangular shape with dimensions below 100 nm will be presented. TEM cross sections of apertures reaching through the metal into silicon will be shown. Optical near-field measurement (wavelength of light 1064 nm) was used to demonstrate the functionality of the SNOM probes. Resolution down to 60 nm (1/17 of wavelength) has been achieved.
Keywords: Atomic force microscopy; Focused ion beam; Nano machining; Scanning near-field optical microscopy